Electrochemical deposition of NiCu alloys in citrate solutions - Vy, Uong Van; Que, Le Xuan (Vietnam Journal of Chemistry, 2017)
This paper presents the research results on electrochemical deposition of NiCu alloy films in containing citrate solutions. Influence of the concentration of the metallic ions to the electrodeposition was studied using linear polarization method. Alloy films have been fabricated by potentiostatic and galvanostatic methods. Element composition and morphology surface of the films was analyzed using EDS and SEM methods. The polarization curves are divided into two distinct regions, the more positive potential than -0.8 V/SCE is the discharge of Cu2+ with the critical current density, the more negative potential than -0.8 V/SCE is the co-discharge of Cu2+ and Ni2+ to alloying of NiCu. The presence of Ni2+ promotes Cu2+ discharge with critical current density at electrode potential -0.4 V/SCE. When the cathode potential decrease causes Ni composition increased and the Cu composition decreased. Cathode current density in the range of -4 to -8 mA/cm2 strong influence on the alloy composition, Ni composition increases with cathode current density.Keywords. NiCu alloy films, electrodeposition, electrodes, hydrogen evolution reaction, alkaline solution. [h1]Hai câu này sai ngữ pháp và không rõ ý tác giả định viết gì để sửa!